Polybenzimidazole mediated N-doping along the inner and outer surfaces of a carbon nanofiber and its oxygen reduction properties - Balan, Beena K.; Manissery, Aiswarya Padinhare; Chaudhari, Harshal D.; Kharul, Ulhas K.; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
Nitrogen-doped (N-doped) hollow carbon nanofiber (CNF) was synthesized by incorporating a nitrogen containing polymer precursor, polybenzimidazole (PBI-BuI), in the inner cavity as well as on the outer walls of the CNF, followed by a high temperature treatment. PBI-BuI incorporation along the inner and outer surface of the CNF was accomplished by synthesizing a low molecular weight polymer by tuning the synthetic parameters. The solution concentration of the PBI-BuI is also varied to facilitate its entry into the CNF by capillary action. The high temperature treatment (700-1000 degrees C) of the resulting CNF-PBI material decomposes the polymer and induces N-doping along the inner and outer surfaces of the CNF. The initial PBI-BuI content and the annealing temperature are also systematically varied to choose the right combination of starting precursors and heat-treatment conditions. Detailed X-ray photoelectron spectroscopy analysis of the samples shows that pyridinic-type nitrogen is the major component in all the samples. Electrochemical characterizations of this material using cyclic voltammetry, rotating disc electrode studies and durability analysis demonstrated that this material can act as a metal-free oxygen reduction electrocatalyst with improved oxygen reduction kinetics and stability. It is also revealed that the onset potential, limiting current density, number of transferred electrons, etc. have a strong dependence on the annealing temperature.